ANTARA MITOS DAN PEDAGOGI: MENGGUGAT RELEVANSI NILAI PENDIDIKAN DALAM ITIHASA DAN PURANA BAGI GENERASI Z - Ayu Pande Sri Kusuma Darmapatni (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to examine the relevance of educational values in Hindu literature, particularly Itihasa and Purana, for Generation Z in the digital era. The study is motivated by the low level of understanding among young people toward the values contained in classical Hindu texts, which are often considered less relevant to modern life. This research uses a qualitative approach with a library research method, supported by hermeneutic, educational axiology, and critical pedagogy approaches. Data were collected through document study and analyzed using content analysis and hermeneutic interpretation. The findings show that Itihasa and Purana contain important educational values such as dharma, satya, ahimsa, and bhakti, which are relevant for character building. However, Generation Z tends to see these texts as myths due to conventional and less contextual teaching methods. Therefore, hermeneutic reinterpretation and contextual pedagogy are needed to make these values more understandable and relevant to young people’s lives. This study confirms that the relevance of Itihasa and Purana depends on how the texts are interpreted and taught in educational practices.